Regional Head Election (Pilkada) Dispute Settlement in the Perspectives of Sociology of Islamic Law - Wagiyanto, M (al-'adalah, 2019)
This article presents an alternative concept of resolving disputes over Regional Head Elections (Pilkada) from the perspectives of the sociology of Islamic Law. The aim is to find the possibility of obtaining better alternative dispute esolutions that meet the feelings of justice of the parties. Up to now, Pilkada dispute resolution always took the path of litigation (court), which ended in victory on the one side and defeat on the other side. Rarely, if ever, there is a dispute settlement that takes a non-litigation path to get a win-win solution. Even though there were no historical documents found in Islamic history on the Regional Head elections; But the absence of the document does not necessarily mean that Islam has no concept that can be used to solve humanitarian problems. As a religion characterized by rahmatan lil alamin (peace upon the world), Islam has a concept that can be applied to resolve disputes that refer to some principles originating from Syari'ah arguments, namely: al-Qur'an, al-Sunnah, Ijmā’ (agreement of the scholars), Qiyās (analogy), Maslahah Mursalah (benefit of society), and ‘Urf (community tradition).